IMPROVING ENGLISH LANGUAGE COMPETENCE OF BIOLOGY EDUCATION STUDENTS THROUGH CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL): A METHODOLOGICAL APPROACH (Ustozlar uchun, 2026)
The rapid internationalization of higher education has increased the need for graduates who possess both professional knowledge and advanced English language competence. In biology teacher education, future teachers are expected to access international scientific literature, communicate professional ideas effectively, and implement innovative teaching methods in multilingual educational settings. However, English instruction in many higher education institutions continues to focus on general language skills rather than discipline-specific communication. This gap limits studentsability to use English for academic and professional purposes.This paper investigates the methodological potential of Content and Language Integrated Learning (CLIL) as an approach to improving English language competence among students majoring in Biology Education. The study analyzes theoretical foundations of CLIL, examines its pedagogical principles, and discusses methodological strategies for integrating biological content with English language instruction. Particular attention is paid to the development of academic vocabulary, scientific communication skills, critical thinking, and learner motivation.